Waste catalyst potential for co-pyrolysis of biomass and single-use plastics: model-free isoconversional kinetics and thermodynamics - Sabah Mariyam (14150859) (2023)
The study aims to investigate the kinetic and thermodynamic characteristics of single and binary pyrolysis of biomass (date pits: DP) and single-use-plastics (polypropylene: PP, and polystyrene: PS), and the effect of adding natural catalysts—seashell (SS) and cuttlebone (CB) for ternary co-pyrolysis of the feeds. The activation energy (Ea) was calculated using different model-free kinetic methods, including Kissinger–Akahira–Sunose (KAS), Ozawa–Flynn–Wall (FWO), and Starink, utilizing information from the degradation at three heating rates from room temperature to 1173 K. The results showed that all three methods produced relatively similar Ea values with a high coefficient of correlation (R2), indicating a good fit for the data. The Ea values for single feeds of DP, PP, and PS using the FWO method were found to be in the range of 196–223 kJ/mol, while for binary feeds—DPPP and DPPPS—the values were found to be lower than for the individual plastics. The high Ea values of the binary plastic mixture are also reduced by ~ 40 kJ/mol in the ternary mixture due to biomass co-pyrolysis. Additionally, the study revealed that the addition of SS and CB catalysts positively affected the ternary co-pyrolysis by reducing activation energy by 28.5 and 5.8%, respectively, due to the catalytic activity of 20 wt% of CaCO3 decomposition from the seashell and cuttlebone added in situ to the feeds. The research contribution of this study lies in its comprehensive investigation of the kinetic and thermodynamic characteristics of biomass and plastic pyrolysis, including single and binary systems, as well as the introduction of natural catalysts for ternary co-pyrolysis. The findings highlight the effectiveness of the studied catalysts in reducing activation energy and provide valuable insights for the development of efficient biomass and plastic waste conversion processes. Other Information Published in: Environment, Development and Sustainability License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s10668-023-03981-9